Глава 14. Оскарження рішень, дій або бездіяльності виконавців та посадових осіб органів державної виконавчої служби до суду цивільної юрисдикції - Малярчук, Любов Сергіївна (Цивільний процес: теорія і практика. Концепції вчених з удосконалення законодавства про цивільне судочинство. Монографія, 2023)
An analysis of the subjects, the procedure and time limits for appealing to a court of civil jurisdiction with a complaint against the decision, action or inaction of a state executor or other official of a state executive service body or a private executor was carried out, and the procedure for consideration of relevant complaints in the civil court procedure was regarded, as well as the procedural form was studied resolution of this issue by the court. The problem of demarcating the jurisdiction of courts regarding the resolution of such categories of cases was studied, in particular, when appealing the decisions of the state executor on the collection of the enforcement fee and the private executor on the collection of the main fee, their decisions on the collection of costs of enforcement proceedings and fines; when filing complaints about decisions, action, inaction in the execution of decisions of non-judicial bodies and other officials, as well as when appealing decisions, actions of inaction in summary executive proceedings and appealing reports of subjects of assessment activity.It is summarized that such an option, which involves determining the jurisdiction of the court precisely by the type of executive document, taking into account which court or other body (official) it was issued, is the most optimal, because all other procedural issues that arise during the execution of the decision in the majority cases are decided according to this criterion. In particular, as we noted at the beginning, this rule should apply to all subjects of enforcement proceedings, and not to further demarcate jurisdiction based on their status. In addition, we do not even consider it expedient to attribute to the competence of administrative courts not only the consideration of complaints against the decisions of the state executor on the collection of the executive fee and the private executor on the collection of the basic remuneration, their decisions on the collection of the costs of the executive proceedings and fines, but also complaints about the decisions, actions, inaction in the execution of decisions of non-judicial bodies and other officials, since a court of civil jurisdiction is also involved in the execution of certain procedural issues. In view of this, it is justified to use a unified approach in all situations related to the enforcement of the decision of the same body or official, and at the same time apply for their settlement to the same court.